2011
DOI: 10.1080/17415993.2011.587519
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of organic sulfides by tetraethylammonium chlorochromate: a kinetic and mechanistic study

Abstract: The oxidation of organic sulfides by quinolinium chlorochromate (QCC) resulted the formation of the corresponding organic sulfoxides. These reactions are first order ones with respect to QCC. A Michaelis-Menten type kinetics was observed with respect to the reactants. The reaction is catalyzed by p-toluene sulfonic acid (TsOH). The oxidation was studied in nineteen different organic solvents. An analysis of the solvent effect on Swain's equation showed that the both cation-and anion-solvating powers of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…223 The Arrhenius expressions for the gas-phase reactions of 1-butene, isobutene, 2-methyl-1-butene, and 3-methyl-1-butene with O 3 were determined, and the reaction rate constant and activation energy agreed with those reported in the literature. 224 The Arrhenius expressions, rate constants, and atmospheric residence times for gas-phase reactions of α- (71) and β-farnesene (72), β-myrcene (73), and β-ocimene (74) with O 3 and • OH radicals using He as the diluent gas were reported. The reactions of αand β-farnesene with • OH radical had no significant temperature dependence.…”
Section: Ozonolysis and Ozonationmentioning
confidence: 99%
“…223 The Arrhenius expressions for the gas-phase reactions of 1-butene, isobutene, 2-methyl-1-butene, and 3-methyl-1-butene with O 3 were determined, and the reaction rate constant and activation energy agreed with those reported in the literature. 224 The Arrhenius expressions, rate constants, and atmospheric residence times for gas-phase reactions of α- (71) and β-farnesene (72), β-myrcene (73), and β-ocimene (74) with O 3 and • OH radicals using He as the diluent gas were reported. The reactions of αand β-farnesene with • OH radical had no significant temperature dependence.…”
Section: Ozonolysis and Ozonationmentioning
confidence: 99%
“…Imidazolium fluorochromate (IFC) is also one of such compounds used for the oxidation of benzylic alcohols 2 . We have been interested in the kinetic and mechanistic aspects of the oxidation by complexed Cr(VI) species and several reports on halochromates have already reported from our laboratory [3][4][5][6] . It is, known that mode of oxidation depends upon the nature of counter-ion attached to the chromium anion.…”
Section: Introductionmentioning
confidence: 99%
“…One of such compounds is tetrakis(pyridine)silver dichromate reported by Firozabadi et al 2 . We have been interested in the kinetic and mechanistic aspects of the oxidation by complex salts of Cr(VI) and several studies have already been reported from our laboratory [3][4][5][6] . It is, known however, that mode of oxidation depends upon the nature of counter-ion attached to the chromium anion.…”
Section: Introductionmentioning
confidence: 99%